2022
DOI: 10.1088/1755-1315/1079/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Fluid Damping in Simplified Models of Pump-Turbines and High Head Francis Runners

Abstract: In order to satisfy the power demand in the electrical grid, hydraulic turbine units frequently work under off-design operation conditions and pass through transient events. These operation conditions can lead to high vibration amplitudes in the turbine runners, decreasing their useful life, and in some cases to premature failures. To determine and to understand the behaviour of the fluid damping is a relevant topic, because this parameter limits the maximum amplitude in resonance conditions. The runner of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In terms of vibration, Cao et al [7] studied the wet mode of the runner under cavitation state, found that cavitation will affect the asymmetry of the added mass matrix. Moraga et al [8], through simplified disc experiments, speculated that the unit speed will affect the fluid damping of rotating components. Some scholars have also attempted specific methods to improve the stability of pump turbine, such as water injection in the vaneless space [9].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of vibration, Cao et al [7] studied the wet mode of the runner under cavitation state, found that cavitation will affect the asymmetry of the added mass matrix. Moraga et al [8], through simplified disc experiments, speculated that the unit speed will affect the fluid damping of rotating components. Some scholars have also attempted specific methods to improve the stability of pump turbine, such as water injection in the vaneless space [9].…”
Section: Introductionmentioning
confidence: 99%